2020
DOI: 10.1111/tpj.14655
|View full text |Cite
|
Sign up to set email alerts
|

PP7L is essential for MAIL1‐mediated transposable element silencing and primary root growth

Abstract: The two paralogous Arabidopsis genes MAINTENANCE OF MERISTEMS (MAIN) and MAINTENANCE OF MERISTEMS LIKE1 (MAIL1) encode a conserved retrotransposon-related plant mobile domain and are known to be required for silencing of transposable elements (TE) and for primary root development. Loss of function of either MAIN or MAIL1 leads to release of heterochromatic TEs, reduced condensation of pericentromeric heterochromatin, cell death of meristem cells and growth arrest of the primary root soon after germination. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Later, it was shown that MAIN and MAIL1 were required for the proper expression of a common subset of genes, as well as TE silencing [ 104 ] ( Figure 1 D). MAIN and MAIL1 physically interact together, as well as with a putative serine/threonine phosphoprotein phosphatase (PPP) called PP7-LIKE (PP7L), and the three mutants show similar developmental and molecular phenotypes, including TE silencing defects [ 107 , 108 ]. Genome-wide level of 5mC is mostly unchanged in main and mail1 mutants, with the notable exception of a slight increase in CHG methylation at pericentromeric regions and in chromosome arm TEs [ 108 ].…”
Section: A Plethora Of Sophisticated Epigenetic Pathways Dampen Tesmentioning
confidence: 99%
“…Later, it was shown that MAIN and MAIL1 were required for the proper expression of a common subset of genes, as well as TE silencing [ 104 ] ( Figure 1 D). MAIN and MAIL1 physically interact together, as well as with a putative serine/threonine phosphoprotein phosphatase (PPP) called PP7-LIKE (PP7L), and the three mutants show similar developmental and molecular phenotypes, including TE silencing defects [ 107 , 108 ]. Genome-wide level of 5mC is mostly unchanged in main and mail1 mutants, with the notable exception of a slight increase in CHG methylation at pericentromeric regions and in chromosome arm TEs [ 108 ].…”
Section: A Plethora Of Sophisticated Epigenetic Pathways Dampen Tesmentioning
confidence: 99%
“…Six paralogs encoding a serine/threonineprotein phosphatase 7 long form-like protein were found in common between germination and longevity and seven of them common to the three traits. This gene (aka MAINTENANCE OF MERISTEMS LIKE-3, MAIL3) participates in transposable element silencing [58]. Additional genes associated with DNA repair (Solyc01g105520.3.1, Solyc01g105530.3.1, Solyc01g109460.3.1) were found among genes correlating with the three traits.…”
Section: Identi Cation Of a Conserved Regulatory Gene Module Associatmentioning
confidence: 99%
“…long form-like protein were found in common between germination and longevity and seven of them common to the three traits. This gene (aka MAINTENANCE OF MERISTEMS LIKE-3, MAIL3) participates in transposable element silencing [58]. Additional genes associated with DNA repair (Solyc01g105520.…”
Section: Identi Cation Of Tissue Speci C Modules Correlating With Phymentioning
confidence: 99%